2003
DOI: 10.1007/s00216-003-1902-5
|View full text |Cite
|
Sign up to set email alerts
|

In-house validation of an improved sample extraction and clean-up method for GC determination of isomers of nervonic acid in meat products

Abstract: An improved extraction and clean-up method for determination of brain-specific fatty acids, in particular lignoceric acid (C24:0) and the cis/ trans isomers of nervonic acid (15 c-t C24:1), in meat products has been developed. The method is based on isolation of the polar lipids of interest from the bulk lipids by solid-phase extraction. The fatty acids, derivatised to their fatty acid methyl esters, are quantified by GC in a DB5 column. Fresh meat samples were extracted by using a mixture of n-butanol:hexane … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Using chromatography, brain-specific fatty acids such as lignoceric acid and the cis/trans isomers of nervonic acid [122,123] had been used as the analyte for the detection of the presence of CNS tissue in meat products through their characteristic component patterns. Spectroscopic techniques are based on the unique absorbance profiles of the sample components at specific wavelengths of the electromagnetic spectrum.…”
Section: Detection Methods For Surveillance Of Prion Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Using chromatography, brain-specific fatty acids such as lignoceric acid and the cis/trans isomers of nervonic acid [122,123] had been used as the analyte for the detection of the presence of CNS tissue in meat products through their characteristic component patterns. Spectroscopic techniques are based on the unique absorbance profiles of the sample components at specific wavelengths of the electromagnetic spectrum.…”
Section: Detection Methods For Surveillance Of Prion Diseasesmentioning
confidence: 99%
“…Biedermann et al [154] analyzed the concentrations of fatty acids typical in bovine CNS, including docosahexaenoic acid (C22:6), lignoceric acid (C24), nervonic acid, and cerebronic acid (C 24 OH), using GC-MS to determine the CNS content The detection limit for CNS using this GC-MS method was 0.01%. In 2003, Agazzi et al [122] reported an enhanced GC method for the detection of isomers of nervonic acid in meat products, reporting that the ratio of the cis/trans isomers of nervonic acid not only exhibit species specificity but also show a significant difference between cow and calf, and between pig and piglet.…”
Section: Nervonic Acidmentioning
confidence: 99%